2017
DOI: 10.1021/acs.jpcc.7b05938
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Modification of Graphene’s Band Structure by Surface Oxygen Atoms

Abstract: We present the spatially resolved modification of the topography and electronic properties of monolayer graphene by a low dosage of atomic oxygen on the nanometer scale. Using the combination of an ultrahigh-vacuum scanning tunneling microscope and a gas beam of oxygen atoms, we show that the surface O-atoms, even at a low coverage of O/C = ∼1/150, serve as p-type dopants that leads to site-dependent partial and full graphene band modifications up to a gap of a few hundred millielectronvolts. The degree of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The red d I /d V curve of Figure 2d shows a wide parabolic shape characteristic of d I /d V measured on an oxygen group. The black d I /d V curve in Figure 2d is flat, with a shoulder at 0.2 eV attributed to a STS conducted on a site with a close‐lying oxygen surrounding as seen in the studies by Harthcock et al and Katano et al [ 33,34 ] d I /d V spectra taken at low temperature (25 K) exhibit a very similar behavior to that shown in Figure 2d (see Figure S3, Supporting Information). The XPS spectrum shown in Figure 2e, of as‐purchased GO flakes deposited from the solution, can be deconvoluted into three main peaks corresponding to CC (284.78 eV, ≈47.08%), CO (287.03 eV, 46.19%), and C = O (288.67 eV, 6.73%) bonds.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…The red d I /d V curve of Figure 2d shows a wide parabolic shape characteristic of d I /d V measured on an oxygen group. The black d I /d V curve in Figure 2d is flat, with a shoulder at 0.2 eV attributed to a STS conducted on a site with a close‐lying oxygen surrounding as seen in the studies by Harthcock et al and Katano et al [ 33,34 ] d I /d V spectra taken at low temperature (25 K) exhibit a very similar behavior to that shown in Figure 2d (see Figure S3, Supporting Information). The XPS spectrum shown in Figure 2e, of as‐purchased GO flakes deposited from the solution, can be deconvoluted into three main peaks corresponding to CC (284.78 eV, ≈47.08%), CO (287.03 eV, 46.19%), and C = O (288.67 eV, 6.73%) bonds.…”
Section: Resultssupporting
confidence: 67%
“…There have been many experimental attempts to image the microscopic structure and extract the microscopic parameters of GO using atomic force microscopy (AFM), [ 23–25 ] high‐resolution transmission electron microscopy (HR‐TEM), [ 26–29 ] scanning transmission electron microscopy (STEM), [ 30,31 ] and scanning tunneling microscopy (STM). [ 32–37 ] Scanning tunneling spectroscopy (STS) measurements were also used to study the local electronic density of states. Katano et al demonstrated that STS spectra taken on unreduced GO deposited on Au exhibit gap energy related to the inhomogeneous size of the sp 2 domains and the charge transfer between the sp 2 domains and the oxygen functional groups attached to the basal plane of the GO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many experimental attempts to see the microscopic structure and microscopic parameters of GO using atomic force microscopy (AFM), [23][24][25] high-resolution transmission electron microscopy (HR-TEM), [26][27][28][29] scanning transmission electron microscopy (STEM), [30,31] and scanning tunneling microscopy (STM). [32][33][34][35][36][37] Scanning tunneling spectroscopy (STS) measurements were also used to study the local electronic density of states. Wang et al showed similarity between the electronic spectrum of RGO and that of pure graphene, as deduced from STS dI/dV curves , [37] thus, suggesting that the residual oxygen groups have limited influence on the final spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Harthcook et al showed that in locally oxidized CVD graphene samples, it is possible to detect different electronic behavior between pure graphene (dI/dV has a "V-shaped") and the proximity of oxygen atoms (dI/dV has a parabolic shape) by local STS probing. [33] Due to the fact that oxygen groups are not arranged in any defined order, and that their distribution depends on synthesis and deposition procedures, the results of these experiments vary widely. For example, Pandey et al, showed by using STM that in RGO sample, [35] oxygen groups were aligned in rows.…”
Section: Introductionmentioning
confidence: 99%